2014
DOI: 10.1212/wnl.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of an inhibitor of RAGE-Aβ interactions in Alzheimer disease

Abstract: Objective: To examine safety, tolerability, and efficacy of PF-04494700, an inhibitor of the receptor for advanced glycation end products (RAGE), in mild to moderate Alzheimer disease (AD).Methods: Double-blind, placebo-controlled trial at 40 academic centers (United States). Subjects with AD and Mini-Mental State Examination score 14-26 were randomized to PF-04494700 60 mg/day 3 6 days, then 20 mg daily (high dose); 15 mg/day 3 6 days, then 5 mg daily (low dose); or placebo, for 18 months. Clinical and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
133
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(135 citation statements)
references
References 23 publications
0
133
0
2
Order By: Relevance
“…The majority of trials (n = 94) used at least one cognitive outcome, 25,27-29, 51,52,55,57,64,66,68,75,78,[86][87][88][89][90][91][92][93]97,104,106,107,110,112,115,118,119,121,123,125,126,130,131,133,134,[137][138][139][140]143,145,146 with a variety of 16 measures used. ADLs were measured in 55 trials, using 12 measures.…”
Section: Published Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of trials (n = 94) used at least one cognitive outcome, 25,27-29, 51,52,55,57,64,66,68,75,78,[86][87][88][89][90][91][92][93]97,104,106,107,110,112,115,118,119,121,123,125,126,130,131,133,134,[137][138][139][140]143,145,146 with a variety of 16 measures used. ADLs were measured in 55 trials, using 12 measures.…”
Section: Published Trialsmentioning
confidence: 99%
“…ADLs were measured in 55 trials, using 12 measures. 27,28,33,37,41,45,46,49,51,52,54,55,57,59,61,63,64,66,68,77,78,81,[85][86][87][88][89][90]92,97,104,[106][107][108][110][111][112]114,115,118,119,[121][122][123][124][125]128,134,135,137,138,[142][143][144][145] Biological markers were measured in 51 trials using a variety of nine biological t...…”
Section: Published Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…TransTech Pharma also developed PF-04494700, which inhibits RAGE/Aβ-42 binding. This agent, which is administered orally, crosses the BBB and helps reduce Aβ accumulation and spatial memory defects [71].…”
Section: High Mobility Group Box 1 Protein (Hmgb1)mentioning
confidence: 99%
“…RAGE ligands can also be used to support diagnoses of AD or PD. Generally, MRI and cerebrospinal fluid (CSF) biomarkers related to AD, do not provide evidence of neurodegenerative change or amyloid clearance [71,72]. However, it has been reported that some RAGE ligands might be useful diagnostic targets.…”
Section: High Mobility Group Box 1 Protein (Hmgb1)mentioning
confidence: 99%